The Sraffian supermultiplier as an alternative closure for heterodox growth theory - Franklin Serrano; Fabio Freitas (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
This paper aims to show that the Sraffian supermultiplier model provides an alternative closure for the heterodox analysis of economic growth. The new closure follows from the assumption of the existence of autonomous non-capacity-creating expenditures, which implies that the ratio of the average to the marginal propensity to save is an endogenous variable whose determination allows the marginal propensity to invest to determine the saving ratio without the need for changes in income distribution. Provided it is also assumed that capitalist competition leads to gradual changes in the marginal propensity to invest in order to adjust productive capacity to demand, the new closure (in contrast to the Cambridge and neo-Kaleckian closures) allows us to reconcile demand-led growth, exogenous distribution, and a tendency towards normal capacity utilization.
Keywords: E11; E12; O41; 330; effective demand; economic growth; income distribution; capacity utilization; theoretical closures